Absorption cross sections for ethane broadened by hydrogen and helium in the 3.3 micron region. (September 2020) - Dodangodage, Randika; Bernath, Peter F.; Zhao, Jianbao; Billinghurst, Brant
Abstract : High resolution absorption spectra of ethane, C2 H6, in the 3.3 µm region (2550–3350 cm − 1 ). Absorption cross sections for ethane broadened by H2 or He. Measurements performed for 203–295 K. Useful for analysis of spectra of giant planets. Abstract: The infrared absorption cross sections of ethane (C2 H6 ) have been measured in the 3.3 µm region by high resolution Fourier transform spectroscopy. The ethane samples had temperatures of 203, 233, 263, 295 K with broadening gas pressures of 10 Torr, 30 Torr and 100 Torr of hydrogen or helium. These cross sections are useful for the interpretation of spectra of the giant planets.